Community-Based Lifelong Education in the Philippines: A Proposed Model in Grassroots Participatory Democracy in Southeast Asia - Arviola, Jr., Serafin A (EDUCARE, 2008)
ABSTRACT: Conflicts among family members, among different groups in the community, and among nations continue to escalate, threatening the survival of the human species. The Philippines is not an exception to these atrocious realities. In this case, Mindanao has experienced one of the most violent armed conflicts in the history of the Philippines. A series of armed confrontations between the government and various Muslim separatist groups have placed the civilian population at the mercy of conflicting parties. Various government programs and projects were initiated to address the problem of war and violence in Mindanao. The study is an attempt to evaluate an existing community-based peace-building program with the aimed to draw out insights on what kind of program suitable for culturally diverse communities that experiences protracted social conflict. The researcher recommends exploring other indicators not included in this study in order to draw out more insights on the dynamics of peace building at the grassroots level.KEY WORDS: conflicts in the Philippines, government programs and projects, community-based lifelong education, and grassroots level.About the Author: Prof. Serafin A. Arviola, Jr. is an Assistant Professor of the Philippine Normal University (PNU). He is currently a Director of Center for Linkages and Extension Services of PNU and a Human Rights Fellow of International Center for Tolerance Education based in New York City. He could be reached at: sarviola2002@yahoo.comHow to cite this article? Arviola, Jr., Serafin A. (2008). âCommunity-Based Lifelong Education in the Philippines: A Proposed Model in Grassroots Participatory Democracy in Southeast Asiaâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.1-16. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 1, 2008); Revised (July 3, 2008); and Published (August 17, 2008).